Evidence of no horizontal or vertical transmission of tomato severe rugose virus by Bemisia tabaci MEAM1 - Favara, Gabriel M.; Bello, Vinicius H. [UNESP]; Rezende, Jorge A. M. (Wiley, 2021)
Bemisia tabaci is important in agriculture worldwide, mainly because it is a vector of numerous plant viruses, probably the most important of which are members of the genus Begomovirus. Dozens of begomoviruses have been reported to infect tomato plants in Brazil, although tomato severe rugose virus (ToSRV) predominates in tomato crops. ToSRV, found so far only in Brazil, is efficiently transmitted by B. tabaci MEAM1. However, no studies have assessed the occurrence of vertical and horizontal transmission of the virus in the insect, which may have epidemiological consequences affecting disease management. This study evaluated the possibility of transmission of ToSRV between whiteflies during copulation and transovarial transmission from viruliferous females of B. tabaci MEAM1 to their progeny. Transmission of ToSRV did not occur during mating between males and females of B. tabaci MEAM1. Aviruliferous males and females confined with viruliferous insects of the opposite sex were also unable to transmit the virus to tomato plants. ToSRV was detected, by PCR, in the ovaries of viruliferous females of B. tabaci MEAM1 but not in eggs, nymphs, or adults of the progeny of viruliferous females. Adult progeny of viruliferous females also did not transmit ToSRV to tomato plants. Together, the results indicate that vertical and horizontal transmission of ToSRV by B. tabaci MEAM1 is unlikely. Sustainable management of the tomato golden mosaic disease caused by ToSRV should continue to focus on using resistant varieties, managing sources of inoculum around tomato fields, and rational chemical control of the vector.
Keywords: begomovirus; horizontal transmission; transovarial transmission; whitefly